Immunomodulatory Phytocompounds from Withania somnifera (L.) Dunal (Ashwagandha) Against COVID-19 - Sarathi Singha, Partha; Ghosh, Ramkrishna; Ghosh, Debosree (Trends in Immunotherapy, 2024)
Withania somnifera is a famous medicinal plant. It is popularly known as Aswagandha. This plant has been in use in Ayurveda and Unani medicine for ages. The medicinal plant has immense medicinal properties. The plant is rich in potent medicinal phytocompounds. These phytocompounds are known to have potent antioxidant, antiviral, antibacterial and immunomodulatory efficacies. Our immune system is the key player in n fighting back any kind of pathogeni attack on us. Withania somnifera extract and certain isolated phytocompounds from the plant are known to boost our immune system. Studies show that the mechanisms of immunomodulatory actions of the bioactive phytocompounds from Withania somnifera are by affecting the various cellular signaling pathways. These primarily involve the signaling pathways associated with the receptors present on the vital immune cells like the dendritic cells, T-cells and B-cells. Thus, some of the compounds of Withania suppress or activate certain components of the innate and adaptive immune system. Unlike synthetic adjuvants, the natural plant derived phytocompounds and their derivatives, as those from the Withania sp. are free from such risk factors. A strong immune system is the best possession to fight back invasions by microbes like bacteria and viruses like the SARS-CoV-2. Detailed and compact knowledge of the compounds from Withania sp. and their mechanism of modulating and impacting our immune system may make the ways for development of new supportive therapies against almost all different types of diseases including COVID 19.